THE INFLUENCE OF BRAND ASSOCIATION ON PURCHASING DECISIONS WITH BRAND AMBASSADORS AS A MODERATING VARIABLE - Dian Wahyuningsih; Nurdin; Dicki Bagus Chandra; Rizal R. Manullang; Zamhari (CV. Adiba Aisha Amira, 2025)
Backgrounds: Researchers have the belief that it is also used as a hypothesis in this research regarding the Brand Association variable which can have a positive relationship and a significant influence on purchasing decisions because the more and better brand associations will make the product more known to the public, regarding product identity and product quality. Objectives In the end, the public/potential consumers can make purchasing decisions. Apart from that, researchers also believe that if the influence of the Brand Association variable on Purchasing Decisions is moderated by the Brand Ambassador variable, it can further strengthen the influence of the Brand Association variable on Purchasing Decisions because Brand Ambassadors will convince buyers of product quality, product suitability, and so on. Methods: This research is quantitative research with an explanatory approach, namely research that uses previous research as a basis for building new arguments to prove the influence of the Independent variable on the Dependent variable and the strength of the moderating variable in strengthening the relationship between the two variables (Kurniawan, 2018). The data used in this research is secondary data distributed digitally to MS Glow consumers spread throughout Indonesia, totaling 300 consumers. These data were analyzed using the Samrt PLS 4.0 analysis tool. Results and Conclusions: The results of table 3 of the path coefficient show a positive relationship direction and a significant influence because the P-Values value is positive and is below the 0.05 significance level, namely 0.021. The results of the second row of the third table of Path Efficiency show a positive relationship direction and a significant influence on Purchasing Decisions because it has a positive direction and is below the 0.05 significance level, namely 0.000, which is more significant than the direct test of 0.021. Thus, the first and second hypotheses in this research can be proven and accepted.